Art : the Definitive Visual Guide - Graham-Dixon, Andrew (London : Dorling Kindersley, 2008)
Derain, André ; Matisse, Henri ; de Vlaminck, Maurice ; Rouault, Georges ; Marquet, Albert ; van Dongen, Kees ; Dufy, Raoul ; Nolde, Emil ; Kirchner, Ernst Ludwig ; Heckel, Erich ; Schmidt-Rottluff, Karl ; Kollwitz, Kathe ; Barlach, Ernst ; Lehmbruck, Wilhelm ; Marc, Franz ; Macke, August ; Jawlensky, Alexej von ; Kokoschka, Oskar ; Schiele, Egon ; Klimt, Gustav ; Braque, Georges ; Picasso, Pablo ; Gris, Juan ; Leger, Fernand ; Fresnaye, Roger de la ; Archipenko, Alexander ; Gleizes, Albert ; Lipchitz, Jacques ; Metzinger, Jean ; Laurens, Henri ; Balla, Giacomo ; Carrà, Carlo ; Severini, Gino ; Boccioni, Umberto ; Russolo, Luigi ; Delaunay, Robert ; Kupka, Frantisek ; Larionov, Mikhail ; Goncharova, Natalia ; Kandinsky, Wassily ; Malevich, Kasimir ; Brancusi, Constantin ; Mondriaan, Piet ; Sickert, Walter ; Gilman, Harold ; Ginner, Charles ; Gore, Spencer ; Bell, Vanessa ; Nevinson, Christopher ; Spencer, Stanley ; John, Gwen ; John, Augustus ; Lewis, Wyndham ; Gaudier-Brzeska, Henri ; Epstein, Jacob ; Roberts, William ; Bomberg, David ; Wadsworth, Edward ; Henri, Robert ; Sloan, John ; Bellows, George ; Demuth, Charles ; Dove, Arthur ; Hartley, Marsden ; Weber, Max ; Wallis, Alfred ; Rousseau, Henri ; Bauchant, André ; Bigaud, Wilson ; Cook, Beryl ; Hyppolite, Hector ; Utrillo, Maurice ; Pascin, Jules ; Chagall, Marc ; de Lempicka, Tamara ; Laurencin, Marie ; Modigliani, Amedeo ; González, Julio ; Soutine, Chaim ; Tatlin, Vladimir ; Gabo, Naum ; Pevsner, Antoine ; Rodchenko, Alexander ; Lissitzky, El ; Torres-Garcia, Joaquin ; Picabia, Francis ; Duchamp, Marcel ; Arp, Hans (Jean) ; Man Ray ; Schwitters, Kurt ; Heartfield, John ; Ernst, Max ; Miro, Joan ; De Chirico, Giorgio ; Masson, Andre ; Delvaux, Paul ; Oppenheim, Meret ; Dali, Salvador ; etc.
boek